Efektivitas Penggunaan Metode Eksperimen dalam Meningkatkan Kemampuan Mengenal Warna di Kelas B RA NW Rensing Bat - Susanti, Yuliana (ALSYS, 2022)
This study aims to improve the ability to recognize colors by using experimental methods. Children basically like to do new things and learn something interesting, namely by experimenting or experimenting, especially at the level of early childhood whose curiosity is very high. This research is a Classroom Action Research (CAR) using qualitative methods. The research data were obtained by using observation, interview and documentation techniques. The increase in the color recognition of students is marked by the increasing number of positive columns filled in for each indicator set. The research obtained is (1) the indicator of "Mentioning Colors" from 28 students, 19 (68%) positive columns filled in the pre-cycle, 22 (79%) columns in the first cycle and 25 (89%) columns in the second cycle, (2) The indicator "Delivering Experimental Results" from 28 students, 12 (42%) positive columns filled in the pre-cycle, 17 (61%) columns in the first cycle and 24 (85%) columns in the second cycle, (3) The indicator "groups colors" from 28 students 15 (64%) positive columns filled in the pre-cycle, 15 (71%) columns in the first cycle and 26 (93%) columns in the second cycle. Based on the results of the study, it can be concluded that the effectiveness of using the experimental method can improve the ability to recognize children's color in Class B RA NW Rensing Bat.